Estudo da evolução microestrutural e das propriedades mecânicas da liga de alta entropia CrMnFeCoNi submetida a processos termomecânicos - Caroline Nazaré Gonçalves (2023)
High entropy alloys (HEAs) are an innovative class of materials that have received significant attention since they were first studied nearly twenty years ago. They consist of combining multiple elements (usually five or more) in nearly equiatomic concentrations, resulting in simple crystalline structures such as body-centered cubic (BCC), face-centered cubic (FCC), and hexagonal close-packed (HCP). The equiatomic alloy CrMnFeCoNi, the most studied HEA to date, is known for Its monophase FCC structure and remarkable mechanical properties at cryogenic temperatures. However, at room temperature, its mechanical strength is lower than many conventional alloys. To improve its mechanical performance, thermomechanical processing strategies, such as cold-rolling followed by annealing, have been employed. Despite this, warm and hotrolling processes, which have similar potential, have been less explored in multicomponent alloys. Therefore, this thesis aimed to fill this knowledge gap by investigating the microstructural and mechanical evolution of the CrMnFeCoNi alloy under these rolling processes, in comparison to the conventional cold-rolling process. Techniques such as scanning and transmission electron microscopy, electron backscatter diffraction, X-ray diffraction, and synchrotron analysis were used to evaluate the microstructure and deformation mechanisms. Vickers microhardness and tensile tests were performed to assess the mechanical properties. The results showed that each process resulted in different microstructural heterogeneities and strengthening mechanisms that influenced the resulting mechanical properties of the CrMnFeCoNi alloy. It was concluded that cold-rolling followed by annealing provides a good combination of strength and ductility attributed to the retention of mechanical twins but requires additional processing steps. Warm-rolling exhibits a good synergy between strength and ductility despite the absence of twins, possibly due to the formation of lamellar substructures. In turn, hot-rolling results in good strength due to the formation of secondphase particles and high ductility due to dynamic recovery and recrystallization.